Technology watch and competitive intelligence for the production of red tilapia (Oreochromis mossambicus) in the department of Huila, Colombia - Camero-Escobar, Guillermo; Calderón-Calderón, Hugo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article shows the results of a technological surveillance and competitive intelligence study about the production of red tilapia (Oreochromis mossambicus), in the Department of Huila, Colombia. The research is qualitative, descriptive and not experimental and the data collection was transversal. The critical monitoring factors correspond to the tilapia culture link, such as: inputs, production systems and seed production, among others. The findings indicate that the research trend has focused on the search for a standardized quality of the physicochemical elements. The basic issues are oriented towards the diet to obtain high protein content, planting densities and evaluation of growth performance. To a lesser extent, research on genetic improvement has been carried out and a field that is beginning to be explored is related to red tilapia byproducts. Regarding the Department of Huila, it is concluded the need to implement strategies that allow producers to appropriate the advances reported in articles and patents, so that employers can make informed decisions to improve the competitiveness of the sector.